Upaya Peningkatan Kreativitas Melalui Kegiatan Kolase Dengan Biji-Bijian Pada Anak Kelompok A Di TK Negeri Pembina Pamotan Rembang Tahun Ajaran 2016/2017 - Witantra, Ganggas; , Drs. Ilham Sunaryo M.Pd (2017)
This study aims to improve the creativity of children in group A at TK Negeri Pembina Pamotan Apex district ajaran2016-2017melalui Year collage activity. This research is a classroom action research (PTK). Subjects in this study were students in group A in TK Negeri Pembina Pamotan Rembang District 2016-2017 school year. This study was conducted in two cycles, each cycle consisting of two meetings. Data from increased creativity collected through observation and field notes. Before the implementation of the results obtained cycle of child reaches 56.52%, and the first cycle of the first meeting at 66.25, the first cycle to the second meeting of 68.83% and cycle II meeting Ke I is 75.36%, and the second cycle II meeting amounting to 84.35% means an increase creativity of pre-cycle, the first cycle and the second cycle, conclusion from this study that through the collage can enhance the creativity of children in group A at TK Negeri Pembina Pamotan Rembang 2016-2017 school year. Keywords : Enhancing Creativity,collage with grain